Map and Trends in International Production on Biology Education - Hugo Juliano Duarte Matias; Barbara Oliveira de Souza (Journal of Research in Mathematics, Science, and Technology Education, 2026)
This study maps publications on biology education in the Web of Science database, aiming to understand its development and the most recent trends. A sample of 422 scientific articles was selected. Their metadata was bibliometrically analyzed using tools from the Bibliometrix statistical package. After reading the abstracts, the articles were categorized according to their type, research participants, thematic focus, and research design. It was found that publications on biology education have been growing, especially after 2014. The three main journals, the ten main authors, and the ten most impactful works in relation to the analyzed corpus are identified. The analyses showed that there is a small group of more prolific authors amidst a large mass of researchers with one or two publications, a proportion that suggests a dispersion of interest in the topic. The most important themes in the structure of academic production are related to “misconceptions” and “evolution,” which are among its motor themes, while descriptors such as “knowledge” and “concepts” stand out among the basic themes of the field. This suggests the importance of discussing the conceptual structure of biological knowledge, highlighting beliefs, attitudes, and the understanding of basic concepts. The thematic structure also reveals a concern with the training of biology teachers. The research reported is mainly survey-based, conducted with higher education students, and refers to teaching strategies or materials and psychological factors related to the teaching-learning process. Given the sample, research in the area is still dispersed among many authors who publish few works and cooperate little, which seems to indicate that the field is still seeking unity.